PENGARUH PEMBERIAN BERBAGI JENIS ABU TERHADAP KETERSEDIAAN HARA NITROGEN PADA TANAH GAMBUT - Muhammad Navarin; Akhmad Rizalli Saidy; Meldia Septiana (Agroekotek View, 2021)
ABSTRACTThis study aims to determine the effect of giving various types of ash on the availability of nitrogen nutrients in peat soil. This research was conducted at the Soil Physics-Chemical Laboratory of the Faculty of Agriculture, Lambung Mangkurat University from June 2020 to August 2020. The experimental research method used was a one-factor completely randomized design (CRD) with 5 treatments and 5 replications. So that there are 25 experimental units. The 5 treatments used were: K = peat without the addition of ash, P = peat + rice husk ash 10ton ha-1, S = peat + oil palm ash 10ton ha-1, AB = peat + coal ash 15ton ha-1, Kp = peat + lime 10ton ha-1. The parameters observed were nitrogen in the form of ammonium (NH4 +) and nitrate (NO3-).ABSTRACT